Complicated acute appendicitis in SARS-Cov-2 infected child - Rzewuska, Anna; Żybowska, Monika; Sielwanowska, Wiktoria; Syzdoł, Bartłomiej; Woźniak, Magdalena (Journal of Education, Health and Sport, 2022)
Background: Appendicitis represents the most common abdominal surgical emergency in children. It is characterized by peri-umbilical pain with migration of the pain to the right iliac fossa, nausea and fever. Recently, an association between acute appendicitis and paediatric inflammatory multisystem syndrome associated with SARS-CoV-2 was suspected. Case report: A 15 year old boy was admitted to surgical clinic due to abdominal pain. Laboratory testing revealed high leukocytosis and neutrophilia. The diagnosis was gangrenous, perforated appendicitis with cecal infiltration. Laparoscopic appendectomy was performed with antibiotic prophylaxis and peritoneal lavage. Two days later, a physical examination revealed costovertebral angle tenderness bilaterally. Urolithiasis was suspected. X-ray examination revealed no shadows in the projection of urinary system and fluid in the right pleural cavity. Then patient developed a fever and dyspnea. A thoracocentesis was performed and about 500 ml of transudate was evacuated again. SARS-CoV-2 was detected in the nasopharyngeal swab RT-PCR. Pleural fluid culture was negative. In the following days about 500 ml of fluid from the pleural cavity was evacuated. In laboratory testing was observed an increase in inflammatory markers.The antibiotic therapy was changed and anticoagulant treatment started. Ultrasonography examinations diagnosed abscess at operated area, which involuted after a few days. The male stopped developing fever, the markers of inflammation gradually decreased and respiratory symptoms were not reported. Conclusions: Analyzing presented clinical report, it can be concluded that COVID-19 infection prolonged the patient's hospitalization and could have contributed to the complications after appendectomy. The patient’s presentations may suggest multisystem inflammatory syndrome potentially associated with COVID-19. Further studies are urgently needed to define the real impact on children health. It may be worth conducting tests for SARS-CoV-2 on children with severe symptoms from the digestive system.